2011
DOI: 10.1074/jbc.m110.135863
|View full text |Cite
|
Sign up to set email alerts
|

Sts1 Plays a Key Role in Targeting Proteasomes to the Nucleus

Abstract: The evidence that nuclear proteins can be degraded by cytosolic proteasomes has received considerable experimental support. However, the presence of proteasome subunits in the nucleus also suggests that protein degradation could occur within this organelle. We determined that Sts1 can target proteasomes to the nucleus and facilitate the degradation of a nuclear protein. Specific sts1 mutants showed reduced nuclear proteasomes at the nonpermissive temperature. In contrast, high expression of Sts1 increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 30 publications
7
62
1
Order By: Relevance
“…Thus, Srp1 is involved in the coupling of proteasomes to ribosomebound nascent chains, and this activity is compromised in Srp1 E145K . It has been suggested that the interaction between Srp1 and the proteasome may be mediated or facilitated by Sts1, a multicopy suppressor of srp1-49 (45,46). We found that the cosedimentation of proteasomes with polysomes significantly decreased in the sts1-2 mutant (Fig.…”
Section: Volume 289 • Number 5 • January 31 2014supporting
confidence: 57%
“…Thus, Srp1 is involved in the coupling of proteasomes to ribosomebound nascent chains, and this activity is compromised in Srp1 E145K . It has been suggested that the interaction between Srp1 and the proteasome may be mediated or facilitated by Sts1, a multicopy suppressor of srp1-49 (45,46). We found that the cosedimentation of proteasomes with polysomes significantly decreased in the sts1-2 mutant (Fig.…”
Section: Volume 289 • Number 5 • January 31 2014supporting
confidence: 57%
“…These observations imply that the yeast 26S proteasome is assembled inside the nucleus from independently imported modules. By contrast, other studies have suggested that the holoenzyme or novel form of the preassembled proteasome undergoes nuclear translocation [22][23][24] . Because the channel of the nuclear pore complex (NPC) can expand to accommodate cargoes with a diameter of up to 39 nm, as revealed by studies using gold particles 25 , it is theoretically possible for intact CP or even the entire 26S proteasome to pass through the NPC.…”
mentioning
confidence: 80%
“…The direction and orientation of translocation might be governed by Sts1, an NLS-containing protein that binds the lid subunit Rpn11 (ref. 22). …”
Section: Pre6-rpt1mentioning
confidence: 99%
“…Isono et al (2007) later confirmed that Rpn2 provides a crucial NLS to aid nuclear import of the RP base and that the lid is separately imported. The nuclear import of the RP lid also requires importin α, though no classical NLS has been identified within RP lid subunits; rather Sts1, a short-lived protein that itself contains a classical NLS, associates with Rpn11 to facilitate nuclear import of the RP lid by importin αβ ( Chen et al , 2011). In accordance, deletion of the Sts1 NLS has downstream effects on the nuclear localization of RP lid in addition to RP base and CP, which suggests that proteasomes could also be transported as holo-enzymes ( Chen & Madura, 2014b).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%